PEMBINAAN IMAN ANAK DI PANTI ASUHAN EL-SHADDAI ABIGAIL PIAYU BERTEMA BERBAGI KASIH, MENYEBAR KEBAHAGIAAN - Purba, Gomgom; Vera Susanti Napitupulu (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Children's faith development at the El-Shaddai Abigail Piayu Orphanage aims to provide a solid foundation in the formation of children's character and personality through the theme